Muscle activity relationships during isometric shoulder internal and external rotation using the ForceFrame dynamometer and athletic shoulder tests in baseball athletes - Ashworth, Ben; Hank, Mikulas; Khaiyat, Omid; Coyles, Ginny; Miratsky, Petr; Verbruggen, Ferdia Falon; Zahalka, Frantisek; Maly, Tomas (Frontiers in Physiology, 2025)
BackgroundOptimal shoulder and trunk neuromuscular coordination significantly contributes to performance and injury prevention in overhead athletes. Although isolated shoulder rotation tests are often discussed in research, they may not fully evaluate the complex muscle synergies necessary for functional thrower positions or force deficiencies. Despite the increasing use of the athletic shoulder (ASH) test in elite sports, evidence regarding the relationship between muscle activation patterns in this multi-joint test and traditional isolated assessments is lacking. This study aimed to examine the muscle activity relationships during shoulder strength assessment of isometric rotation and the ASH test in overhead throwing athletes.MethodsSurface electromyography was used to analyze the muscle activation of nine shoulder and trunk muscles during maximal voluntary contractions in 17 male national team baseball athletes. Normalized values were used in muscle activation relationship analysis between internal/external rotation and ASH test’s three shoulder positions in the dominant arm (ASH I, ASH Y, and ASH T).ResultsAnalysis between internal rotation, external rotation, and the ASH I, ASH Y, and ASH T test positions showed significant differences in muscle activity (p < 0.05). The infraspinatus, anterior and posterior deltoid, and upper trapezius demonstrated higher activity in the shoulder rotation tests, while the external obliques and pectoralis major indicated higher activity during ASH tests. Moderate (ρ = 0.40–0.69) correlations were found between muscles during the tests, while strong (ρ = 0.70–0.89)-to-very strong (ρ = 0.90–1.00) correlations were found between individual muscles.ConclusionThe ASH and shoulder rotational tests’ results showed different shoulder and trunk neuromuscular activation levels, demonstrating a low relationship between the prime movers for ASH positions and muscles activated during shoulder rotation. This implies that muscle synergies vary significantly depending on joint positioning and test mechanics. It also emphasizes the importance of using multiple test batteries to capture force production deficits and abnormalities that are relevant to overhead athletes. The results support rehabilitation progression starting with infraspinatus strengthening in neutral shoulder abduction, followed by scapular stabilizer training at wider abduction angles to restore functional overhead capacity. Acute or chronic performance may be monitored weekly for further training optimization, return-to-sport decisions, and injury prevention in elite overhead throwing athletes.